MIGRASI PEDAGANG DAN PENGRAJIN EMAS NAGARI GUGUAK TINGGI TABEK SAROJO (STUDI KASUS MIGRASI KE PASAR RAYA KOTA PADANG) - Muhammad Ridho; Ahyuni ahyuni (JURNAL BUANA, 2019)
This research aims to determine the driving factors, pullers, and barriers of gold traders and craftsmen from the Guguak Tinggi Tabek Sarojo area to migrate to Padang City, especially to Pasar Raya Kota Padang. The type of research used is qualitative descriptive research. The results of the study show that (1) the driving factor for migration is the lack of availability of jobs in the area of ​​origin, wanting to gain new experiences and insights, finding relationships to use artisan skills, and customs and habits of migrants (2) attractive factors in employment relating to gold processing, high gold purchasing power (3) the factor that is a barrier to migration is the desire to care for parents and care for homes in the village and have a network that provides capital in the form of gold and there are already customers to market the results of gold processing in the form of rings, necklaces, pendants, bracelets, so there is no interest in migrating to other places.